Roles of Melatonin in Goat Hair Follicle Stem Cell Proliferation and Pluripotency Through Regulating the Wnt Signaling Pathway - Zhang, Weidong (Front Cell Dev Biol, 2021)
Emerging studies show that melatonin promotes cashmere development through hypodermic implantation. However, the impact and underlying mechanisms are currently unknown. In vitro study has previously demonstrated that melatonin induces cashmere growth by regulating the proliferation of goat secondary hair follicle stem cells (gsHFSCs), but there is limited information concerning the effects of melatonin on cell pluripotency. It is also known that Wnt signaling may actively participate in regulating cell proliferation and stem cell pluripotency. Therefore, in the current investigation, goat hair follicle stem cells were exposed to multiple concentrations of melatonin and different culture times to reveal the relationship between melatonin and the activation of Wnt signaling. A proportionally high Catenin beta-1 (CTNNB1) response was induced by 500 ng/L of melatonin, but it was then suppressed with the dosages over 1,000 ng/L. Greater amounts of CTNNB1 entered the cell nuclei by extending the exposure time to 72 h, which activated transcription factor 4/lymphoid enhancer-binding factor 1 and promoted the expression of the proliferation-related genes C-MYC, C-JUN, and CYCLIND1. Moreover, nuclear receptor ROR-alpha (RORα) and bone morphogenetic protein 4 (BMP4) were employed to analyze the underlying mechanism. RORα presented a sluggish concentration/time-dependent rise, but BMP4 was increased dramatically by melatonin exposure, which revealed that melatonin might participate in regulating the pluripotency of hair follicle stem cells. Interestingly, NOGGIN, which is a BMP antagonist and highly relevant to cell stemness, was also stimulated by melatonin. These findings demonstrated that melatonin exposure and/or NOGGIN overexpression in hair follicle stem cells might promote the expression of pluripotency markers Homeobox protein NANOG, Organic cation/carnitine transporter 4, and Hematopoietic progenitor cell antigen CD34. Our findings here provided a comprehensive view of Wnt signaling in melatonin stimulated cells and melatonin mediated stemness of gsHFSCs by regulating NOGGIN, which demonstrates a regulatory mechanism of melatonin enhancement on the growth of cashmere.